The effect of skin tension, needle diameter and insertion velocity on the fracture properties of porcine tissue. (November 2021) - Irwin, T.; Speirs, A.; Merrett, C.
Abstract: Using metal needles to penetrate skin tissue is common in medical treatments for the delivery of medication or minimally invasive surgery. In most applications the fracture properties of skin tissue is not important as the human surgeon has full control over the needle. Given that robotically controlled surgeries and self applied medical devices have become increasingly popular, a better understanding of the fracture properties and how to mathematically model the fracture process is needed. Experiments measuring the force required to fracture porcine skin tissue were done while varying the applied skin tension, needle insertion speed and needle diameter. The applied skin tension was found to have the greatest influence on the fracture properties, while the insertion speed was found to have a negligible impact. The variance in experimental results was not well explained by the three independent variables alone, suggesting that additional parameters influence the fracture process.